The Arens Algebras of Vector-Valued Functions - I. G. Ganiev; O. I. Egamberdiev (Journal of Function Spaces)
A class of Arens algebras of vector Banach algebra valued functions is considered. It is shown that Arens algebra of vector-valued functions is complete locally convex metrizable algebra.